Android based mobile growth app “AmiGrow” to support early diagnosis of stunting and growth delays of toddlers - Ngaisyah, Dewi; Hiswati, Marselina Endah; Mindarsih, Eko; Lestari, Nia Rizqi (BKM Public Health and Community Medicine, 2021)
Objective The prevalence of stunting toddlers in Indonesia is still in high rate at 27.6%, the largest prevalence compared to other nutritional problems. Moreover, stunting problems can have a direct impact on growth delays. One of the efforts to control these issues is monitoring toddler’s growth and progress, so the expert can do early diagnosis if stunting and growth delays are found. Utilization of android-based mobile growth application (AmiGrow) is an application that supports early diagnosis of stunting and growth delays of toddlers. Method: AmiGrow mobile application is developed with user-centered design (UCD) method using 8th Java development kit, android studio, visual studio code, and flutter framework Result: the app has run according to its function, with well received responses (35.6%) and very good responses (64.4%) by toddler’s mothers. Conclusion: mobile growth AmiGrow app is useful for supporting early diagnosis of stunting and developmental delays for toddlers in digital way.